Noetika románu Empusion Olgy Tokarczukové – variace čapkovské a kunderovské - Radomil Novák (Studia Slavica)
This study describes and interprets the ways and possibilities of knowing the world and one’s own identity in Olga Tokarczuk’s novel Empusion. It draws on fundamental understandings of noetics as a philosophical discipline and the possibilities of knowing the world through a work of literature (literary epistemology), and it explores parallels with the ideas of Milan Kundera and Karel Čapek. The aim of the study is to demonstrate the cognitive value of Tokarczuk’s work, to describe the stable elements of her poetics, and to show her ability to seek “novelistic” possibilities of discussion about current issues in the contemporary world.